Thrombin activatable fibrinolysis inhibitor (TAFI) and markers of endothelial cell injury in dialyzed patients with diabetic nephropathy - Małyszko, Jolanta; Małyszko, Jacek S.; Hryszko, Tomasz; Myśliwiec, Michał (Thrombosis and Haemostasis, 2004)
Patients dialyzed due to diabetic nephropathy are at a higher risk of death due to cardiovascular complications than dialyzed non-diabetic patients. Disturbances in hemostasis may play a role in the vascular complications of diabetes mellitus. It has been postulated that TAFI-thrombin activatable fibrinolysis inhibitor, which couples two opposite systems: coagulation and fibrinolysis, may be involved in the mechanism of vascular endothelial damage in diabetic patients. We assessed: TAFI and TAFIa, markers of ongoing coagulation: thrombin-antithrombin complexes, prothrombin fragments 1+2, a marker of ongoing fibrinolysis: plasmin-antiplasmin complexes in diabetic and non-diabetic patients on hemodialyses-HD, peritoneal dialysesCAPD, patietns with chronic renal failure with and without diabetic nephropathy on conservative treatment. Both groups of dialyzed diabetic patients have a higher concentration of markers of ongoing coagulation and TAFI activity when compared to dialyzed non-diabetic patients. Linear regression analysis showed that TAFI concentration was directly related to albumin in HD and CAPD patients without diabetic nephropathy, whereas TAFIa correlated with triglycerides, fibrinogen and leukocytes count in this group. When evaluated separately (HD, CAPD), significant correlations between TAFIa and triglycerides and fibrinogen were found only in diabetic CAPD patients. Multivariate analysis showed no correlation between TAFI and other parameters studied. In conclusion, elevated circulating TAFI and TAFIa might be a new link in the pathogenesis of impaired fibrinolysis in diabetic nephropathy, and thus atherosclerosis progression, particularly in CAPD patients. Hypercoagulable state observed in diabetic patients on conservative treatment and maintained on dialyses may contribute to the higher cardiovascular mortality in this population. In these patients there is also evidence of endothelial injury, and probably secondary activation of the coagulation cascade.
Keywords: TAFI; diabetic nephropathy; hemodialyses; peritoneal dialyses; endothelium